2005
DOI: 10.1002/pola.20592
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific sequential block copolymerizations of styrene and 1,3‐butadiene with a C5Me5TiMe3/B(C6F5)3/Al(oct)3 catalyst

Abstract: This article reports a new methodology for preparing highly stereoregular styrene (ST)/1,3-butadiene (BD) block copolymers, composed of syndiotactic polystyrene (syn-PS) segments chemically bonded with cis-polybutadiene (cis-PB) segments, through a stereospecific sequential block copolymerization of ST with BD in the presence of a C 5 Me 5 TiMe 3 /B(C 6 F 5 ) 3 /Al(oct) 3 catalyst. The first polymerization step, conducted in toluene at Ϫ25°C, was attributed to the syndiospecific living polymerization of ST. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The strong and sharp peak appearing at 145.9 ppm confirmed that the graft copolymers were highly syndiotactic 12, 13. Figure 4(A) shows the peaks at 21.4 ppm derived from methyl carbon in MS.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…The strong and sharp peak appearing at 145.9 ppm confirmed that the graft copolymers were highly syndiotactic 12, 13. Figure 4(A) shows the peaks at 21.4 ppm derived from methyl carbon in MS.…”
Section: Resultsmentioning
confidence: 85%
“…Figure 4(B–D) reveals during the anionic grafting reaction a qualitative decrease in the peak intensity at 21.4 ppm and a corresponding qualitative increase in the peak intensity of the PB units at 27.5 ppm. This peak proved that PB was highly cis‐1,4 12, 13. If the grafting reaction had been complete, the 13 C‐NMR peak at 21.4 ppm should have disappeared completely, and the intensity of the peak at 27.5 ppm should have reached its maximum.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations